2014
DOI: 10.1002/jip.1434
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the ‘Angels of Death’: Conceptualising the Contemporary Nurse Healthcare Serial Killer

Abstract: Focusing specifically upon nurses who commit serial murder within a hospital setting, this paper aims to establish insights into this particular subcategory of healthcare serial killer. In addition, the paper aims to test the usefulness of an existing checklist of behaviours among this group of serial murderers. Drawing upon existing lists of healthcare serial killers produced by other scholars as well as legal records and an online news archive, we identified and researched healthcare serial killer nurses, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…1 gibt einen Überblick. Weltweit sind 57 Tötungsserien dokumentiert: 19 weitere in Europa, 18 in den USA und Südamerika, 4 in Japan, 3 in Australien und 1 in Kanada 4 5 6 7 8 9 .…”
Section: Einführungunclassified
See 1 more Smart Citation
“…1 gibt einen Überblick. Weltweit sind 57 Tötungsserien dokumentiert: 19 weitere in Europa, 18 in den USA und Südamerika, 4 in Japan, 3 in Australien und 1 in Kanada 4 5 6 7 8 9 .…”
Section: Einführungunclassified
“…Table 1 provides an overview. Worldwide, 57 similar serial murders have been documented: 19 in Europe, 18 in the USA and South America, 4 in Japan, 3 in Australia, and 1 in Canada 4 5 6 7 8 9 .…”
Section: Introductionmentioning
confidence: 97%
“…She was found guilty of the attempted murder of three other children and of causing grievous bodily harm to six more. Referred to in the media coverage as the "Angel of Death" (a term not unique to Allitt), she secured a place in British popular history as one of the country's most prolific women serial killers (Yardley and Wilson, 2016). In the press coverage of her trial, it was widely reported that Allitt's actions resulted from Munchausen's Syndrome By Proxy (MSBP) -a "psychological disorder" in which the carer seeks attention by inducing illness in their child or charge (Polledri, 1996: 551).…”
Section: Beverley Allitt Self-starvation and Media Narratives Of Criminal Femininitymentioning
confidence: 99%
“…Although Allitt was sometimes constructed as simply an appalling one-off (a "monster" beyond the boundaries of social intelligibility) (Morrissey, 2003: 25), it is the relationship between Allitt, gender, and everyday constructions of anorexia that is of interest here, particularly in terms of how her image contributed to cultural discourses on self-starvation and femininity at the time. In addition, despite her notoriety in the British context, there is surprisingly little scholarship on Allitt, and she largely appears as a reference in research on the healthcare serial killer (Yardley and Wilson, 2016), or as a brief case study in works on gender and murder (D'Cruze, Walkate and Pegg, 2006;Seale, 2010). In focusing on how Allitt's identity as an (eating) disordered woman was mediated and how this intersected with popular and legal discourses on her crimes, this article also contributes to feminist scholarship on the cultural construction of women's criminality, especially in terms of the narrative of the "damaged personality" and how this is offered as an explanatory framework for women who kill (Seal, 2010: 50).…”
Section: Beverley Allitt Self-starvation and Media Narratives Of Criminal Femininitymentioning
confidence: 99%
See 1 more Smart Citation